Atuação dos profissionais de saúde no cuidado paliativo à pessoa idosa desospitalizada em município de tríplice fronteiria - Silva, Muriel Gracelli Pereira da (2024)
This is an exploratory field study, with a qualitative approach, conducted in the municipality of Foz do Iguaçu, on the border with Paraguay and Argentina. The general objective was to analyze the understanding and practices of healthcare professionals regarding Palliative Care (PC) for elderly patients discharged from hospitals in a border region. Semi-structured interviews were conducted with nine healthcare professionals, six from the Home Care Service (HCS), and three from a Long-Term Care Institution for the Elderly (LTCI). The study is relevant for expanding knowledge about the experiences of healthcare professionals in Foz do Iguaçu, enabling reflections on public policies in PC, and highlighting the importance of a multidisciplinary and culturally sensitive approach to the needs of the elderly. The interviews took place from October 7 to December 5, 2023, with two participants from the pilot test and the professionals from the HCS and LTCI. The interview data were systematized according to the thematic analysis proposed by Minayo. Six thematic areas were identified: Palliative care: an introduction to the topic; Palliative care practice; Interprofessional work in palliative care; Palliative care for the elderly; Death in the context of palliative care; and Perspective on palliative care. To discuss the results, the theoretical framework of the principles guiding PC was used. The results show that professionals recognize PC as a humanized approach to the process of illness and death. Empathy, although not formally recognized as an intrinsic value of PC, is considered essential by professionals, influencing the quality of care. In both hospital and LTCI settings, professionals rely on medical guidelines to initiate PC, which most often begins in the hospital context. Despite the high demand and the limited number of professionals working in the HCS, the team manages to discuss elderly care; in contrast, in the LTCI, interactions among professionals are limited to information exchanges. Although the majority (66.6%, n=6) of the interviewees do not perceive significant differences in providing PC to the elderly, the results revealed variations such as a higher demand for care compared to younger individuals, and some resistance to the intergenerational role exchange. The ethnic and cultural diversity that characterizes the study field presents challenges to the healthcare team, particularly regarding communication and addressing spirituality and the end of life across different cultures. Professionals view death as a natural part of the life cycle and face the challenge of discussing end-of-life issues with patients and their families. There seems to be a greater difficulty in finding professionals willing to provide PC to the elderly, particularly due to challenges in dealing with the subject of death. The results point to the challenges faced in hospital discharge, including the burden on healthcare professionals and family caregivers, and the shortage of professionals. It is concluded that PC is essential for improving the quality of life of elderly patients discharged from hospitals, particularly in border regions. In this context, the HCS and LTCI facilitate this discharge process. It is recommended to establish local training strategies to increase the number of professionals qualified in PC to ensure adequate access to PC.